Avaliação das provas de interpretação de texto com foco nas habilidades de leitura - Robson Santos de Carvalho (2014)
This thesis investigates students performance in reading comprehension questions formulated by elementary school teachers, focusing on reading abilities. Such questions were created during continuing education courses that took place in public schools in 11 cities from the south of the state of Minas Gerais, from 2007 to 2011. These tests were given to 2,306 students. In the first quarter of 2013, 138 students from two state schools in Alfenas, MG, were given 392 questions to measure different reading skills. The research shows a relationship between the students performance and the way the questions were formulated. Aiming to assess the efficiency of tests as a guide element to pedagogical actions that focus on developing reading skills and to verify which are the strategies/skills used by students to answers the tests questions, this research was divided into two stages, corresponding to two data Groups. On the first Group, we analyzed questions from reading tests that were created according to the SIMAVE Skills Reference Matrix relating textual aspects such as a texts logical-discursive relations marked by conjunctions, adverbs and other connectives; repetitions or references made using pronouns, ellipses and other referencing resources; global inferences and contextual meaning inferences of words or expressions. The second Group was based on reading skills assessment questions created by students from UNIFAL-MG that participated in the PIBID program, focusing on the strategies/skills students used to answer such questions. A contrast between both data Groups was established, showing that the students used their skills, knowledge and strategies regardless of the way the questions were created. We investigated the reading skills that were evaluated by the tests the teachers had created, and we defined the students performance per test, and per skill. Reading abilities were classified by their degree of difficulty, and the strategies/abilities the students used to answer the questions were ascertained. The analyses, conceptions of kinds of texts, and the textuality and textualization are based on Text Linguistics and on academic references on assessment. The results show that the abilities mentioned on the SIMAVE skills reference matrix are indispensible to assure the students reading competence, and also indicate the Skills Diagnostic Assessment as a privileged tool in the process of teaching reading in schools.